UPAYA MENINGKATKAN KEPUTUSAN PENGGUNAAN MEETING PACKAGE DI HOTEL BUMI ASIH JAYA BANDUNG MELALUI DEMAND BASED PRICING METHODS (Survei pada Tamu Wisatawan Bisnis Pengambil Keputusan Penggunaan Meeting Package Di Hotel Bumi Asih Jaya Bandung) - Fauzan, Mohamad; Setiyorini, Heri Puspito Diyah (THE Journal : Tourism and Hospitality Essentials Journal, 2011)
Tourism is an industry thath as the potential to become an instrument of increasing foreign exchange earnings. The sector is evolving as it has become a necessary to travel along with the development of tourism social-culture undergoing changes. One of the tourism industry that is always growing increasingly is hospitality industry. Especially in hotel industry. Competitionin hotel industry in Indonesia, especially Bandungkeep growing fast. The key to success in the hotel management not only in terms of services but also from elements of the products and pricing. Those become an valuable asset it self and important in general. Hotel Bumi Asih Jaya Bandung is one of three stars hotel which always strive to provide variety of products through pricing approach. Demand-based pricing method pricing methods that focus on the customer's perspectiveis consistent with the pricing on the customer's perception of value to affect the decision of using meeting package. As the above background, the research conducted on the effects of demand-based pricing methods toeard to purchase decisionof meeting package. The purpose of this study was to determine how the demand-based pricing methods and purchase decision of meeting package at Hotel Bumi Asih Jaya Bandung, and to know how bigthe influence of demand-based pricing methods toward to purchase decision of meeting package. This study is descriptive and verifikatif, while the method is a descriptive survey and survey eksplanatory. Samples takenin this study population as many as 48 people. Sampling techniqueis carried out the census. Data processing is done using parametric statistical test which uses the formula path analysis via SPSS11.5 for Windows. The results showed that the dimensions of demand-based pricing methods that get the highest ratings on the dimensions of the buyer based pricing. While making use of sub-variables that get the highest ratings at the time of use. Demand based pricing methods that consist of buyers based pricing, psychologicalpricing, and negotiation has a positive effect amounting against the decisions of the use of meeting package at Hotel Bumi Asih Jaya Bandung, which means the better the demand-based pricing methods that have the higher the usage decision meetings package is formed.